Pengaruh Pijat Oksitosin Terhadap Kelancaran Asi Minggu Pertama Post Partum di Tempat Praktek Bidan M - Ulfah, Mariyah (Universitas Malahayati, 2023)
ABSTRACT Background Mother's Milk (ASI) is God's gift for babies that cannot be replaced by any food or drink. Oxytocin massage can be done in conditions where the mother's breasts are swollen or not smooth, and in cases where the mother wants to relax. Oxytocin massage is an act of spinal massage starting from nerves 5-6 to the scapula which will speed up the work of the parasympathetic nerves to convey commands to the back of the brain so that oxytocin comes out. Basic Health Research (RISKESDAS) data for 2021, 52.5 percent – or only half of the 2.3 million babies aged less than six months – are receiving exclusive breastfeeding in Indonesia, or a decrease of 12 percent from the 2019 rate. The rate of early initiation of breastfeeding (IMD) also fell from 58.2 percent in 2019 to 48.6 percent in 2021. The aim of the study was to determine the effect of oxytocin massage on the smoothness of the first week of breastfeeding in post partum mothers at the practice of Midwife M. The research methodology for this type of research is a quasy experiment with a Pre Test - Post Test Control Group Design approach. The sample technique used was a total sampling of 40 respondents who observed breastfeeding at PMB Midwife M. Research Results Based on the t-test, a p-value <0.05 (0.000) was obtained, which means that there was a significant effect between oxytocin massage and breastfeeding in post partum mothers at PMB Midwife M in the first week postpartum. Conclusions and suggestions There is a significant effect between oxytocin massage and breastfeeding in post partum mothers at PMB Midwife M in the first week post partum. In order for the production of breast milk to be abundant, it is necessary to take actions such as oxytocin massage so that the mother feels comfortable so that the mother can provide exclusive breastfeeding. Keywords: Breastfeeding, Oxytocin Massage, Post Partum Mothers ABSTRAK Air Susu Ibu (ASI) adalah anugerah Tuhan untuk bayi yang tidak dapat digantikan oleh makanan atau minuman apapun. Pijat oksitosin dapat dilakukan pada keadaan payudara ibu yang bengkak, atau tidak lancar, dan pada kasus ibu yang ingin relaksasi. Pijat oksitosin adalah suatu tindakan pemijatan tulang belakang mulai dari nervus 5-6 sampai skapula yang akan mempercepat kerja syaraf parasimpatis untuk menyampaikan perintah ke otak bagian belakang sehingga oksitosin keluar. data Riset Kesehatan Dasar (RISKESDAS) 2021, 52,5 persen – atau hanya setengah dari 2,3 juta bayi berusia kurang dari enam bulan- yang mendapat ASI eksklusif di Indonesia, atau menurun 12 persen dari angka di tahun 2019. Angka inisiasi menyusui dini (IMD) juga turun dari 58,2 persen pada tahun 2019 menjadi 48,6 persen pada tahun 2021. Mengetahui pengaruh pijat oksitosin terhadap kelancaran ASI minggu pertama pada ibu post partum di tempat praktek Bidan M. Jenis penelitian ini adalah quasy experimen dengan pendekatan Pre Test -Post Test Control Group Design. Tehnik sampel yang digunakan adalah total sampling sebanyak 40 responden yang dilakukan observasi pengeluaran ASI di PMB Bidan M. Berdasarkan uji t-test didapatkan nilai p value < 0,05 (0,000) yang artinya ada pengaruh yang signifikan antara pijat oksitosin dengan pengeluaran ASI pada ibu post partum di PMB Bidan M di minggu pertama post partum. Ada pengaruh yang signifikan antara pijat oksitosin dengan pengeluaran ASI pada ibu post partum di PMB Bidan M di minggu pertama post partum. Agar produksi ASI dapat melimpah maka perlu dilakukan tindakan seperti pijat oksitosin agar ibu merasa nyaman sehingga ibu dapat memberikan ASI Eksklusif. Kata Kunci: Pengeluaran ASI, Pijat Oksitosin, Ibu Post Partum